The Arts Interview. Rick Boland : On Stage - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Division of Educational Technology)
Newfoundland actor Rick Boland talks with host Fred Hollingshurst about his theatrical performances and why he chose acting. A Memorial University Television Production Condition: Good